기관지확장증이 있는 16세 여자 환자의 비결핵 항산균 폐질환 - 송유선; 정혜인; 이보라; 허희재; 고원중; 김지현; 안강모; 경예찬 (Allergy asthma & respiratory disease, 2020)
Nontuberculous mycobacterial (NTM) pulmonary disease generally occurs in old people with underlying lung disease. However, unlike adults, NTM infections in children with normal immunity are rare, and they occasionally manifest as lymphadenitis. We herein present a rare case of NTM pulmonary disease in a girl who is the youngest patient reported in Korea. A 16-year-old female was brought to the hospital because of dyspnea on exertion, fever, and productive cough. The patient had bronchiectasis. She underwent Fontan operation for right isomerism, double outlet right ventricle, pulmonary stenosis, and had been taking prophylactic antibiotics for asplenia. NTM were found in the sputum and bronchoalveolar lavage fluid by acid fast bacillus (AFB) staining and culture, which were identified as Mycobacterium avium. The treatment started with azithromycin, ethambutol and rifampicin. After 6 months of treatment, respiratory symptoms improved and the sputum AFB culture became negative. She is currently on medication with above-mentioned drugs for 10 months without any adverse effects. This case suggests that NTM pulmonary disease should be suspected and properly treated especially in children and adolescents with underlying lung disease. KCI Citation Count: 0